Integrated primary care for mental health in the Thiruvananthapuram District, Kerala State (World Health organisation, 2008)
Since 1999, Thiruvananthapuram District has been integrating mental health services into primary care. Trained medical officers diagnose and treat mental disorders as part of their gen- eral primary care functions. A multidisciplinary district mental health team provides outreach clinical services, including direct management of complex cases and in-service training and support of primary care workers. The free and ready availability of psychotropic medications in the clinics has enabled patients to receive treatment in their communities, thus greatly reduc- ing expenses and time spent travelling to hospitals. Starting in 2002, primary care centres began to assume responsibility for operating their men- tal health clinics with minimal support from the mental health team. Currently, mental health clinics are operating in 22 locations throughout the district. Services provided include diagno- sis and treatment planning for newly-identified patients, review and follow-up for established patients, counselling by the clinical psychologist or psychiatrist, psychoeducation and refer- rals as needed.